Legal Analysis of Paylater Transactions from a Contemporary Fiqh Perspective - Yeti Dewanti; Alicia Fadillah; Dede Putri Sari; Bob Belowo; Ali Mahsun; M. Hasbi As-Siddiq (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
The development of financial technology has introduced PayLater as a digital payment innovation allowing consumers to acquire goods first with deferred payment. This convenience has driven increased PayLater usage in Indonesia, especially among younger generations, while simultaneously raising Islamic legal issues related to contracts, interest, late penalties, and uncertainty (gharar). This study aims to analyze the legal status of PayLater transactions from a contemporary fiqh perspective by examining fiqh muamalah principles, DSN-MUI fatwas, and contemporary scholarly opinions. The research employs a qualitative approach with library research methodology, collecting data from national and international scientific journals (2022–2026), DSN-MUI fatwas, fiqh muamalah books, and related literature, then analyzing them using descriptive and content analysis techniques. The findings reveal that the legal status of PayLater is conditional, depending on the contract form and its compliance with Sharia principles. Transactions containing riba, gharar, and exploitative penalties contradict Islamic law, whereas financing systems based on Sharia contracts such as murabahah and wakalah bil ujrah have the potential to serve as alternatives aligned with contemporary fiqh values. This study recommends developing Sharia-based PayLater that is transparent, just, and oriented toward public welfare in accordance with maqāṣid al-syarī'ah.